Analisis Nilai Tukar Nelayan (NTN) Alat Tangkap Sungkur Udang Rebon (Acetes indicus) Di Kecamatan Toboali - Kurniawan; Ferni Anjani Putri; Muhammad Bachtiyar (Jurnal Airaha, 2021)
This study was aimed to obtain the fisherman terms of trade with rebon shrimp scoop net fishing gear and the factors which affect the fisherman terms of trade. This study was conducted in October to December 2020. This study used interview and FGD (Focus Group Discussion) methods. The data analysis used a descriptive method. The results of this study showed that the FTT of scoop net fisherman income in October was up to 19.23, 13.27 in November, and 6.41 in December. The FTT of fishery in October was up to 277.42, 194.31 in November, and 121.81 in December. Some factors that affected the FTT of scoop net fishing gear were the fisherman age, education level, number of family dependents, duration of being fisherman, selling price of rebon shrimp, and fishing season. This study concluded that scoop net fisherman FTT decreased within study substance in October to December 2020.